Blended Learning Through The Lens of Students' Perspectives - Sianipar, Rimma (Afeksi: Jurnal Penelitian dan Evaluasi Pendidikan, 2025)
The present study investigates students’ perceptions of the implementation of blended learning at Universitas Negeri Makassar. Utilizing a mixed-methods design, data were collected from 60 students through questionnaires and semi-structured interviews. Quantitative findings indicate that blended learning fosters autonomy in managing learning time, with 58% of respondents strongly agreeing and 25% agreeing. Additionally, 50% strongly agreed and 25% agreed that the model supports independent learning. A majority of students also found learning materials to be easily accessible online (47% strongly agree, 30% agree). However, only 37% of respondents strongly agreed and 33% agreed that they felt comfortable participating in online discussions, suggesting some degree of communication challenges. While student–lecturer interaction was perceived as generally well-maintained, it did not receive ratings as high as other aspects. Qualitative data further supported these findings, revealing that blended learning enhances learner independence and digital competence, yet also highlighting the need for strategies to promote more meaningful interaction. Overall, the study confirms that blended learning contributes to greater flexibility and accessibility in higher education but calls for more interactive approaches to strengthen student lecturer engagement.